Export Barriers and Export Performance of Vietnamese Seafood Firms Targeting International Market - Tran, Huu Ai (University of Economics Ho Chi Minh City, 2023)
The purpose of this paper is to identify key export barriers and their impact on performance of Vietnamese seafood firms with their export to the US market. By reviewing the literature and using expert opinions, five factors of the export barriers can be identified, including product, price, distribution, logistics, and promotion. A structured questionnaire is used to survey managers of 152 seafood firms, and exploratory factor analysis, used to categorize variables in five barrier dimensions. Then, the development of linear regression aims to determine which barrier has a greater negative effect on export performance. The empirical results suggest that except for promotion, the other barriers have significantly negative impact on export performance. Based on the relative importance of the different marketing barriers, seafood firms should firstly focus on quality improvements to improve their performance.